On the Feasibility of Decentralized Grid Scheduling - Fiscato, Marco; Costa, Paolo; Pierre, Guillaume (The International Workshop on Decentralized Self Management For Grids, P2P, And User Communities (Selfman'08), co-located with IEEE SASO'08, Venice, Italy, October 2008., 2008)
Many authors recognize the limitations of hierarchical Grid scheduling in scalable environments, and proposed peer-to-peer solutions to this problem. However, most peer-to-peer grid resource management systems allow only to discover available resources at the time of the request. We claim that peer-to-peer techniques have the potential for actual Grid scheduling, where each resource maintains a schedule of its future allocation to jobs. We present such a protocol, which additionally allows users to specify desired properties about the requested schedules.